Effect of display lighting on fresh pork longissimus packaged in oxygen-permeable and oxygen-barrier films - Hung, S.; Hunt, Melvin C.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Longissimus samples from seven pork loins were used to determine display color stability when packaged in oxygen-permeable (polyviny lchloride, PVC) film and when vacuum packaged. Color scores were different at all times when evaluation was done under display lighting, with poorest color under Cool White and most desirable color under NAFA or Grolux Wide Spectrum. Since differences were minor or non-existent when evaluation was under a common light, we conclude that a different color rendition caused the differences noted and no photochemical effect occurred.
Keywords: Swine; Lighting; Longissimus; Oxygen-permeable films; Oxygen-barrier films